Chlorophyll–a/ZnO Nanorod Based Hybrid Photoanodes for Enhanced Photoelectrochemical Splitting of Water. Issue 5 (21st February 2017) - Prasad, Mohit; Sharma, Vidhika; Mayabadi, Azam; Rokade, Avinash; Pawbake, Amit; Rondiya, Sachin; Waykar, Ravindra; Jadhavar, Ashok; Pathan, Habib; Jadkar, Sandesh
Abstract: We report synthesis and use of Chlorophyll‐a/ZnO nanorod based hybrid photoanodes for photoelectrohemical (PEC) activity. Hybrid photoanodes consist of vertically oriented self ordered nanorod array of ZnO fabricated via electrodeposition followed by sensitization with chlorophyll‐a. Under AM 1.5 illumination (100 W/cm 2 ), at 0.75 V bias, the hybrid photoanodes achieved a photocurrent density of 0.67 mA/cm 2 which is ∼2.6 times increase over bare ZnO nanorods (0.26 mA/cm 2 ). To the best of our knowledge, this is the first report on the use of Chlorophyll‐a/ZnO nanorod based hybrid electrodes in photoelectrochemical cells, with potential applications in switching and sensing. Abstract : Chl‐A/ZnO nanorods synthesized using electrodeposition route has potential to be utilized for photoelectrochemical water splitting and switching applications.